Risk of proximal femoral nail antirotation (PFNA) implant failure upon different lateral femoral wall thickness in intertrochanteric fracture: a finite element analysis. Issue 5 (4th April 2022) - Zheng, Liqin; Wong, Duo Wai-Chi; Chen, Xinmin; Chen, Yuanzhuang; Li, Pengfei
Abstract: Proximal Femoral Nail Antirotation (PFNA) has been commonly used to treat intertrochanteric fractures, despite the risk of implant failure. The integrity of the femur could influence the risk of implant failure. This study evaluated the influence of lateral femoral wall thickness on the potential of implant failure. A finite element model of the hip was reconstructed from the Computed Tomography of a female patient. Five intertrochanteric fracture models at different lateral femoral wall thickness (T1 = 27.6 mm, T2 = 25.4 mm, T3 = 23.4 mm, T4 = 21.4 mm, and T5 = 19.3 mm) were then created and fixed with PFNA. We simulated a critical loading condition by a high loading case during walking. Elastoplastic material models with yield stress and failure strain were applied to the bone and implant in which breakage can be simulated using the element deletion function. In addition, the stress and displacement of the implant and femur were analysed. Implant breakage occurred at the sides of the proximal nail canal in cases of T4 and T5 which was further supported by the higher maximum von Mises stress and nail displacement. The increased stress and displacement of the implant may implicate a reduction of stability and risk of implant failure. We suggested that precaution shall be taken when the wall thickness was less than 21.4 mm.